No Higher Law : American Foreign Policy and the Western Hemisphere since 1776 - Loveman, Brian (Book collections on Project MUSE., 2010)
From the nation's earliest days, argues Brian Loveman, U.S. leaders viewed and treated Latin America as a crucible in which to test foreign policy and from which to expand American global influence. Loveman demonstrates how the main doctrines and policies adopted for the Western Hemisphere were exported, with modifications, to other world regions as the United States pursued its self-defined global mission. This revisionist view considers the impact of slavery, racism, ethnic cleansing against Native Americans, debates on immigration, trade and tariffs, the historical growth of the military-in.